Ring, Patrick and Scott 1. Interview about traditional music. - Carroll, Kayla (2013)
Interview with traditional musicians Patrick Ring and his great-nephew, Scott Ring. Topics include reasons for learning to play, repertoire and style, memories of music in Quidi Vidi, part 1. "Introductions and how they are related; 1:30 - PR talks about his brother Jim’s involvement in radio show “Irene B. Mellon”; Listening to program as a child; Picking up accordion himself; 3:27 - Trying to play at 6 years old at family card games; Memory of playing at 4AM and waking family; Memories of parties at the house; Couples waltzing to PR’s music at 7 years old and getting money from a “collection plate”; 5:56 - Mummering in Quidi Vidi; Playing for mummers; Songs played; 7:32 - Going to school in Quidi Vidi; walking to St. Patrick’s Hall for high school; 8:10 - Memories of PR’s father humming songs; Playing for dances, parties, and Church functions; 9:46 - PR’s repertoire “Irish tradition”; 10:31 - SR’s musical start playing clarinet in Junior High; Classical music; Taking lessons from Ray Walsh; Playing jazz music; Learning to play tin whistle; 1989 first trip to Ireland;12:38 - SR first listening to traditional music when living in Toronto; Keeping in touch with home through music; Recorded on over 25 albums; 13:28 - SR “I don’t know where I’d be without music”; 13:35 - SR coming to family at 16 due to parent’s divorce; Keeping strong hold on “Ring” roots because he was separated;15:00 - Picture of Randy Ring and Jim “Skipper” Ring as inspiration for Scott; Verses from song Scott wrote based on that picture; 16:46 - Regatta rowing; Playing song “9:12:04”; PR talks about steering in Regatta; Steering at Mundy Pond races; Parties after races; 20:34 - Regatta song “Up the Pond” a recording of Jim Ring; SR plays tune on flute; Quidi Vidi Minstrels and Quidi Vidi Caleidgh bands; Explanation of term “Caleidgh”; 23:20 - SR playing in St. John’s; being recognized as Jim Ring’s grandson; Playing professionally in Calgary; Moving from jazz to traditional music; SR’s band “Cowboy Celtic”; International awards; 25:57 - SR ...